Nucleic Acid-Based Diagnostic Tests for the Detection SARS-CoV-2: An Update - Choo Yee Yu; Kok Gan Chan; Chan Yean Yean; Geik Yong Ang (Diagnostics, 2021)
The coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) began as a cluster of pneumonia cases in Wuhan, China before spreading to over 200 countries and territories on six continents in less than six months. Despite rigorous global containment and quarantine efforts to limit the transmission of the virus, COVID-19 cases and deaths have continued to increase, leaving devastating impacts on the lives of many with far-reaching effects on the global society, economy and healthcare system. With over 43 million cases and 1.1 million deaths recorded worldwide, accurate and rapid diagnosis continues to be a cornerstone of pandemic control. In this review, we aim to present an objective overview of the latest nucleic acid-based diagnostic tests for the detection of SARS-CoV-2 that have been authorized by the Food and Drug Administration (FDA) under emergency use authorization (EUA) as of 31 October 2020. We systematically summarize and compare the principles, technologies, protocols and performance characteristics of amplification- and sequencing-based tests that have become alternatives to the CDC 2019-nCoV Real-Time RT-PCR Diagnostic Panel. We highlight the notable features of the tests including authorized settings, along with the advantages and disadvantages of the tests. We conclude with a brief discussion on the current challenges and future perspectives of COVID-19 diagnostics.